Molecular profiling of thymoma with myasthenia gravis: Risk factors of developing myasthenia gravis in thymoma patients. (January 2020) - Lee, Ming-Ching; Hsiao, Tzu-Hung; Chuang, Han-Ni; Lee, Li-Wen; Chi, Pei-Ling; Tsai, Hui-Mei; Mao, Chien-Lin; Hsu, Chung-Ping
Highlights: There are 136 up- and 4 down-regulation genes in thymoma associated MG compared to non-MG thymoma. In thymoma with MG, HIF3A, IGFBP1, KLF15, and PDK4 were significantly up-regulated comparing to non-MG thymoma. The expression of HIF3A in thymoma involved in the development of MG. Abstract: Objective: Thymoma is a rare epithelial tumor arising from the thymus in the anterior mediastinum. Nearly 50% of patients with thymoma develop myasthenia gravis, which is an indication of a poor long-term prognosis. Here, we identified specific and effective molecular markers for predicting in the development of myasthenia gravis patients with thymoma. Material and methods: We investigated molecular profiling based on RNA-sequencing (RNA-seq) for myasthenia gravis development in patients with thymoma. RNA was extracted from 34 patients with thymoma, 16 of whom had myasthenic and 18 of whom did not, and transcriptome profiles were analyzed through next-generation sequencing. Results: We discovered 140 differential expressed genes associated with myasthenia gravis in thymoma patients. The four genes, hypoxia-inducible factor 3 alpha (HIF3A), insulin-like growth factor-binding protein 1, pyruvate dehydrogenase kinase, and Krüppel-like factor 15 were differentially expressed in patients with thymoma who has myasthenia gravis and were validated by quantitative polymerase chain reaction. HIF3A expression was significantly higher in patients with myasthenia gravis than in those without. Conclusion: HIF3A is aberrantly expressed in patient with thymoma who has myasthenia gravis and may be involved in the development of myasthenia gravis in thymoma patient.